COMPETENCY-BASED TEACHER EDUCATION AND TEACHING ENGLISH AS A FOREIGN LANGUAGE: Perceptions of Faculty and Administrators of the English Departments at Teachers Colleges in Indonesia - ABDULHAMIED, Fuad (1982)
The Indonesian Department of Education and Culture is currently in the process of disseminating the concepts of competency-based teacher education (CBTE) to be eventually implemented in teachers colleges. In this initial stage, perceptions of CBTE held by the people directly involved would be worthy of study. Besides, the English programs, because of the role of the English in the development of the country, need special attention. Hence, the purpose of this study was the ascertainment of the perceptions of faculty and administrators of the Indonesian teachers colleges regarding CBTE in relation to teaching English as a foreign language (TEFL). Eighteen English departments at state teachers colleges were contacted, fifteen of which participated in the study. Analysis of variance, multiple regression, and Pearson product-moment correlation were utilized to analyze the data using procedures in the Statistical Analysis System. The respondents, overall, perceived CBTE favorably. The only variable associated with a significant difference in CBTE perceptions was institutional types: the Institutes of Teacher Training and Education respondents perceived CBTE less favorably than the Faculties of Teacher Training respondents. The audio-lingual and cognitive approaches were selected to represent TEFL. On the audio-lingual approach the respondents revealed agreement with a slight tendency toward "undecided". A greater degree of agreement was shown on the cognitive approach. Significant differences were found in the audio-lingual approach perceptions when the respondents were categorized by highest degree, teaching experience, training abroad, academic rank, institutional type, and departmental student enrollment. Significant linear-relationships were also found between the combined personal, academic, and institutional variables and each set of CBTE and TEFL perceptions. Significant correlations did exist too among the perceptions of CBTE, the audio-lingual approach, and the cognitive approach. It was implied that implementation of CBTE in the English programs would run smoothly, that the audio-lingual and cognitive approaches would fit nicely in the English programs based on CBTE, and that the approaches to TEFL should be accomodated in relative parity. The current status of the English departments needs to be investigated as to readiness for coping with the potentially adaptable CBTE and TEFL principles.